Higher employee commitment by targeted motivation - Kozák, Anita (Studia Mundi – Economica, 2020)
The aim of the study is to present the relationship between the identified motivational type of self-determination theory and the three-component model of employee commitment (affective, continuous, normative) and professional commitment. We used the method of questionnaire survey, we conducted primary research among the students and professional partners of the Faculty of Economics and Social Sciences of Eszterházy Károly University. The basic population of our research was examined for 410 respondents. In order to analyze the data we used the SPSS statistical program. In addition to the methods of descriptive statistics, we used non-parametric tests (Mann-Whitney) and correlation (Spearman rank correlation). Our results did not confirm the previous researchers experience, namely managers affective, normative and professional commitment are higher than subordinates’. Also, managers are more motivated than subordinates. Examining the correlation between commitment and motivation, we also found different results among the group of manager and subordinates. The relationship between amotivation and affective, continuous and professional commitment is stronger in the case of managers than subordinates. In addition, the relationship between external regulation and affective, continuous and normative commitment is stronger in the case of subordinates than managers.